Distinct geographic parthenogenesis in spite of niche conservatism and a single ploidy level: A case of Rubus ser. Glandulosi (Rosaceae) - Sochor, Michal; Duchoslav, Martin; Forejtová, Věra; Hroneš, Michal; Konečná, Michaela; Trávníček, Bohumil (The New phytologist, 2024)
Asexual organisms often differ in their geographic distributions from their sexual relatives. This phenomenon, termed geographic parthenogenesis, has long been known, but the underlying factors behind its diverse patterns have been under dispute. Particularly problematic is an association between asexuality and polyploidy in most taxa. Here, we present a new system of geographic parthenogenesis on the tetraploid level, promising new insights into this complex topic. We used flow cytometric seed screen and microsatellite genotyping to characterise the patterns of distribution of sexuals and apomicts and genotypic distributions in Rubus ser. Glandulosi across its range. Ecological modelling and local-scale vegetation and soil analyses were used to test for niche differentiation between the reproductive groups. Apomicts were detected only in North-western Europe, sexuals in the rest of the range in Europe and West Asia, with a sharp borderline stretched across Central Europe. Despite that, we found no significant differences in ecological niches. Genotypic richness distributions suggested independence of the reproductive groups and a secondary contact. We argue that unless a niche differentiation (resulting from polyploidy and/or hybridity) evolves, the main factors behind the patterns of geographic parthenogenesis in plants are phylogeographic history and neutral microevolutionary processes, such as clonal turnover.
Keywords: apomixis; Rubus ser. Glandulosi; niche differentiation; partenogeneze; Parthenogenesis; Polyploidy; Apomixis; ploidie; Ploidies; geographical parthenogenesis; apomixie; genotypic diversity; Rubus; clonal turnover; polyploidie